ASSESSMENT SYSTEM TO DETERMINE THE MAJOR IN SMK 3 TANGERANG USING VISUAL BASIC 6.0 - Seno Adi Nugroho (Jurnal Sistem Informasi, 2007)
Scientific writing contains a description of the assessment system to determine the direction for students of SMK N 3 which sits in semester 1 class with 2 by using Microsoft Visual Basic 6.0. As for who should fill the first time on this program is to form students and the value. In this program penjurusan Parent Student Number (NIS) is the next key that will lead to students penjurusan process. Calculation process in determining this direction is by dividing the total value of some of the relevant subjects with the number of subjects so that the results obtained Index Options Program (IPP). From the IPP is to be processed and eventually will determine the direction for students.